2015
DOI: 10.1002/pra2.2015.145052010078
|View full text |Cite
|
Sign up to set email alerts
|

How does knowledge management affect service innovation in academic libraries?: A survey study

Abstract: Effective management of all knowledge produced within an organization is frequently identified as a key criteria for innovation of new products and services within the organization. Academic libraries are beginning to realize the importance of knowledge management (KM) in this regard. However, there aren't any quantitative studies studying KM and service innovation in the context of libraries. Islam, Agarwal and Ikeda came up with a framework for knowledge management for service innovation in academic librarie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Thus, the KM process appears related to the use, creation, and dissemination of knowledge to enable organizations to obtain CAs that make them survive in this increasingly competitive economy [71]. Several studies have confirmed to examine the relationship between the company's knowledge management and service innovation, and there are a relationship and the results of several studies that state that Knowledge Management has a positive influence on the Service Innovation [7], [14], [15], [72]. Based on the elucidation above, it means that the higher the organization's ability to provide the right solution with a Knowledge Management Capability strategy that can provide added value to the organization, high-level innovation will appear better in the face of service innovation in the telecommunications industry.…”
Section: B Knowledge Management (Km) In Service Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the KM process appears related to the use, creation, and dissemination of knowledge to enable organizations to obtain CAs that make them survive in this increasingly competitive economy [71]. Several studies have confirmed to examine the relationship between the company's knowledge management and service innovation, and there are a relationship and the results of several studies that state that Knowledge Management has a positive influence on the Service Innovation [7], [14], [15], [72]. Based on the elucidation above, it means that the higher the organization's ability to provide the right solution with a Knowledge Management Capability strategy that can provide added value to the organization, high-level innovation will appear better in the face of service innovation in the telecommunications industry.…”
Section: B Knowledge Management (Km) In Service Innovationmentioning
confidence: 99%
“…Knowledge increased quicker than before, experience, and evaluation of the population in business and generated in an organization for innovation of new products and services in the Telco industry [6]. Changes triggered by way of disruption technology, increasing customer needs, and shrinking budgets have resulted in innovation needed through every organization [7]. Some research has reaffirmed its importance to knowledge management (KM) performs a function in improving innovation and organizational performance [3], [8]- [12].…”
Section: Introductionmentioning
confidence: 99%
“…Akram et al, 2011;Páez-Logreira et al, 2016;Zia and Shafiq, 2017). The synthesis and application of knowledge captured is deemed crucial to improving existing services as well as to developing new services in academic libraries (Islam et al, 2015a(Islam et al, , 2015b.…”
Section: Introductionmentioning
confidence: 99%